2007
DOI: 10.1080/13880200701498879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Antioxidative Power and Anticancer Activity in Herbs from Traditional Chinese Medicine Formulae with Anticancer Therapeutic Effect

Abstract: Lobeliae chinensis Herba (''ban bian lian''), Rheum officinale Baill. (''da huang''), Sanguisorba officinalis Linn. (''di yu''), Agrimonia pilosa Ledeb. (''xian he cao''), and Paris polyphylla Smith (''zhi hua tou'') are well-known traditional Chinese medicines. They are commonly used in traditional Chinese medicine formulae against cancer. In this study, the antioxidant and anticancer effects of water extracts of these herbs were investigated. In the antioxidant and anticancer studies, water extracts of di yu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 16 publications
2
41
0
1
Order By: Relevance
“…In fact, antioxidants could reduce the risk of cancers, aging, atherosclerosis and other oxidants-induced diseases. Thus, antioxidants can protect living organisms from oxidative damage caused by reactive oxygen species (Li et al, 2007). Medicinal plants with antioxidant and anticancer (Li et al, 2007;Charoensin, 2014); and with anticancer and antimicrobial (Tamokou et al, 2013) activities have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, antioxidants could reduce the risk of cancers, aging, atherosclerosis and other oxidants-induced diseases. Thus, antioxidants can protect living organisms from oxidative damage caused by reactive oxygen species (Li et al, 2007). Medicinal plants with antioxidant and anticancer (Li et al, 2007;Charoensin, 2014); and with anticancer and antimicrobial (Tamokou et al, 2013) activities have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, antioxidants can protect living organisms from oxidative damage caused by reactive oxygen species (Li et al, 2007). Medicinal plants with antioxidant and anticancer (Li et al, 2007;Charoensin, 2014); and with anticancer and antimicrobial (Tamokou et al, 2013) activities have been reported. In addition, a variety of medicinal plants have been documented to exert dual actions as antimicrobials and antioxidants (Prachayasittikul et al, 2008(Prachayasittikul et al, , 2009(Prachayasittikul et al, , 2010(Prachayasittikul et al, , 2012Treeratanapiboon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor cells can still survive under extreme conditions such as low oxygen and carbohydrate availability due to their relatively high tolerance to hostile environments. Similar to other herbs Li et al, 2007), Panax ginseng has reported to have anticancer effects both in vitro and in vivo Ni et al, 2010;Qi et al, 2010). The ability of Panax ginseng on cancer prevention was illustrated by a recent cohort study, in which Korean Red Ginseng (KRG) extract powder (1 g) was administered orally to each patient (n=643) with atrophic gastritis per week for 3 years and reports were followed up for 8 years (Yun et al, 2010).…”
Section: Sexual Arousal In Menopausal Womenmentioning
confidence: 99%
“…The absorbance (A original ) of individual compounds in methanol (without DPPH added) was measured so as to eliminate the "color interference" of each compound. The percentage free radical scavenging capacity (expressed as SR %) was calculated using the following equation (Li et al, 2007):…”
Section: Measurement Of Free Radical Scavenging Capacitymentioning
confidence: 99%
“…In contrast to most western medicines in which the therapeutic strategies are mainly based on the cause-and-effect principle (Li et al, 2007), the philosophy of the uses of TCM are simply based on a holistic and spatial perception of the individual with the environment (i.e., it is a quest for an overall restoration of the "upset equilibrium" of our body). Thus, with a completely different philosophical/therapeutic approach, TCM provides therapeutic effects through a multi-target organ strategy with an array of different mechanisms.…”
Section: Introductionmentioning
confidence: 99%